PERANCANGAN MESIN REMAS (SQUEEZE MACHINE) UNTUK TERAPI AUTISME - Raswan, Awan; Suryo, Sumar Hadi; Jamari, Jamari; Haryanto, Ismoyo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
The last two decades, in the world of autism increased dramatically. In 1990 obtained 4 from 10000 births (1: 2500). In 2000 to 2008 be 1: 88, increased nearly 30 fold. Deep pressure therapy is a method of providing the pressure and the amount of time on the outside of the body most deeply and evenly. Deep pressure generated by stress relieving device, such as squeeze machine. Squeeze machine can give the effect of calmness to the people hypersensitive to sensory stimulation, such as autism. In Indonesia, squeeze machine is still rare because the price is quite expensive. As needed, it should be designed at an affordable price without compromising quality. Phase of the design process, namely: (1) project definition, project planning, and preparation of technical specifications of the product, (2) the design concept of the product, (3) designing embodiment product, and (4) preparation of documents for the manufacture of products. Squeeze machine model design concept originated from the use of the prone position, deep pressure of a V shaped wall. Squeeze machine design usage position supine position, deep pressure of the three arms, namely: (1) hand and body, (2) the hip and thigh, and (3) the lower leg. For ages under 8 - 9 years, deep pressure 30 - 40 psi within 15 - 45 minutes. At the end of the design process gained some documents as the basis for the manufacture of prototypes, namely: (1) layout drawing, (2) arrangement drawing (assembly), (3) detail element drawing, and (4) the bill of materials.